A benzothiazolium-derived colorimetric and fluorescent chemosensor for detection of Hg2+ ions - Nhan, Doan Thanh; Hien, Nguyen Khoa; Ai Nhung, Nguyen Thi; Binh, Nguyen Van; Bao, Nguyen Chi; Quang, Duong Tuan (Vietnam Journal of Chemistry, 2016)
A benzothiazolium-derived colorimetric and fluorescent chemosensor (L) for detection of mercury ions has been prepared. The detection limits of the colorimetric and fluorescent method for mercury ions are 15.3 and 11.8 ppb, respectively, much lower than the reported chemosensors based on similar derivatives of benzothiazolium. The optimized molecular structures, absorption and fluorescence characteristics of the chemosensor and its complex with mercury ions were carried out using the calculations at the B3LYP/LanL2DZ level of theory, combination with Atoms in Molecules and Natural Bond Orbitals analyses.